Optimization of the Mixing of Hibiscus Flower (Hibiscus rose sinensis) Extract as a Lip Balm Color with Variations in Concentration - Kumala Sari, Diah Indah; Mayangsari, Fransisca Dita; Pratiwi, Elasari Dwi (Universitas Muhammadiyah Yogyakarta, 2023)
Hibiscus rosa sinensis L. is widely used by the community to decorate the garden because of its splendor. In addition, Hibiscus flowers containing anthocyanin and flavonoids have antioxidants, which function as antioxidants against free radicals. This natural dye can be obtained by extracting Hibiscus flowers through maceration using 96% ethanol. In this research, Hibiscus flowers were obtained from Sendang Rejo Village, Lamongan Regency. In the extract process, the Hibiscus flower’s petals were blended until smooth, then added to 96% ethanol (1 liter) and stirred for 30 minutes. Filtrate results were taken, placed in a porcelain dish, and put in an oven at 60 °C for a day. Four formulas were made with varying levels of Hibiscus flower extract: F1 (0%), F2 (2%), F3 (4%), and F4 (6%). Physical evaluation included organoleptic, homogeneity, dispersibility, pH, and qualitative tests for the identification of anthocyanins. The results of the organoleptic, homogeneity, dispersion, pH, and identification of anthocyanins evaluations were then analyzed descriptively. The data from the organoleptic test indicated that F1 had an odorless white color, while F2, F3, and F4 had a red and white color with a distinctive Hibiscus flower aroma. The homogeneity test revealed that while F1 had good homogeneity, F2, F3, and F4 were not homogeneous (heterogeneous). The spreadability test on the four formulas did not fall within the range of requirements, namely 5-7 cm, with an average value of 3.53, but this was related to several significant reasons. In addition, the pH test results matched the requirements for topical preparations, namely 4.5–6.5, with an average value of 5.075. In conclusion, Hibiscus flower extract obtained through the maceration method with 96% ethanol could not give a homogeneous red color from the anthocyanin substance. Physical evaluation and anthocyanin identification tests also obtained good results.